2021
DOI: 10.1016/j.celrep.2021.109208
|View full text |Cite
|
Sign up to set email alerts
|

Generation of excitatory and inhibitory neurons from common progenitors via Notch signaling in the cerebellum

Abstract: Highlights d GABAergic and glutamatergic cerebellar neurons are generated from Sox2 + progenitors d Single Sox2 + ECPs can give rise to both excitatory and inhibitory cerebellar neurons d Notch activity mediates GABAergic versus glutamatergic cell fates in Sox2 + ECPs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 79 publications
2
19
0
Order By: Relevance
“…3, A to C; and fig. S11, A to C), in accord with previous reports ( 34 ). We additionally identified a Gsx1 + population that we traced to the anterior ventricular zone (fig.…”
Section: Progenitor Heterogeneity Reflects Cell Fate Decisionssupporting
confidence: 92%
“…3, A to C; and fig. S11, A to C), in accord with previous reports ( 34 ). We additionally identified a Gsx1 + population that we traced to the anterior ventricular zone (fig.…”
Section: Progenitor Heterogeneity Reflects Cell Fate Decisionssupporting
confidence: 92%
“…This same bias was first reported by Cepko and colleagues (Jadhav et al, 2006), and they proposed a model in which low levels of Notch promote photoreceptor development, while intermediate levels of Notch signaling causes the MPCs to generate other types of retinal neurons (e.g., ACs and HCs). Recent evidence has shown that like the MPCs of retina, cerebellar progenitors give rise to both inhibitory and excitatory lineages, and the level of Notch signaling determines the fate: cells with low levels of Notch signaling adopt the excitatory fate, while cells with intermediate levels of Notch activity develop as inhibitory neurons (Zhang et al, 2021). Although the mechanism by which this occurs is not understood, the differences we observe in chromatin accessibility near the PTF1A gene suggest that the failure to engage these sites after complete Notch inhibition may in part underlie this difference.…”
Section: Discussionmentioning
confidence: 99%
“…2c). Finally, GM11, which included genes encoding Notch signalling ligands ( Dll1 , Dll3 ) and effectors ( Hes6 ) promoting neurogenesis 26, 27 , was upregulated in committed enteric neuronal precursors emerging at different stages of mouse and human development (Fig. 2a; Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%